Radiologische Diagnosen im Migrationskontext: Infektionskrankheiten - Stojković, Marija; Müller, Jan; Junghanss, Thomas; Weber, Tim (RöFo, 2018)
Globalization and emigration impact on the spectrum of diseases challenging health care systems. Medical practitioners have to particularly prepare for infectious diseases. Methods The database of a health care center specialized on tropical medicine was screened for patients with history of migration and one of the following diagnoses: Cystic echinococcosis, tuberculosis, schistosomiasis, visceral leishmaniosis, and neurocysticercosis. Representative casuistics were prepared from select case histories. Radiological pertinent knowledge was compiled based on literature search. Results A small selection of frequently imported infectious diseases covers a considerable fraction of health care problems associated with migration. For cystic echinococcosis, schistosomiasis, and neurocysticercosis imaging is the most relevant diagnostic procedure defining also disease stages. Tuberculosis and visceral leishmaniosis are important differentials for malignant diseases. Conclusion Imaging plays a meaningful role in diagnosis, treatment stratification, and follow-up of imported infectious diseases. Radiological skills concerning these diseases are important for providing health care for patients in context of migration. Key Points Citation Format
Online-Publikation: 28.12.2017
Gesehen am 27.08.2020